Image Quality Assessment of In-House Phantom for Pediatric Computed Tomography - Audiena Gelung Prayitno; Dafa Miftahuddin; Aditya Prayugo Hariyanto; M. Roslan A Gani; Endarko (Jurnal Fisika dan Aplikasinya, 2025)
Computed tomography (CT) offers several advantages. However, it involves a high dose of radiation exposure. In pediatric CT scans, reducing the radiation dose can lead to increased noise and lower image quality. Generally, there is a significant relationship between radiation dose and diagnostic image quality. This research investigates and analyzes the correlation between low-dose radiation and image quality in pediatric CT scans. This study used in house pediatric phantoms (7 year). Twelve artificial cylinder targets were fabricated with diameters 3, 5, 8, and 10 mm, and CT densities +100, -400, -750 HU. The image quality was performedusing CT-Scan 128 slice with parameters of helical scanning using a low dose and standard dose and using 80 and 120 kV. For Signal noise to ratio (SNR), Contrast to Noise Ratio (CNR), Volumetric CT dose index (CTDIvol), SizeSpecific Dose Estimates (SSDE) also investigated. The effective value of the diameter for 7 years was 20.15 cm. Findings suggest, SSDE for in-house pediatric phantoms was found to be 3.71 mGy for low dose and 6.09 for standard dose. For image quality analysis, the low-dose CT protocol has a detection sensitivity of 100% for targets measuring > 5mm in diameter.